The perspective of nurses towards euthanasia and assisted suicide: a review article - Alireza Yousefy; Habibalah Rezaei; Amin Beigzadeh (Report of Health Care, 2015)
Euthanasia or assisted suicide is a contentious issue that provokes substantial clinical and ethical debate. Nurses have a key role in caring for end-of-life patients. They are also often involved in euthanasia or assisted suicide. Therefore, we aimed to assess the attitudes of nurses concerning this controversial topic in order to highlight the present debate about it. In particular, the nurses’ involvement in this practice based on some background factors were emphasized. In our review, we used articles published on the topic of euthanasia and assisted suicide in nursing profession. In this regard, all abstracts and full papers were read critically and the relevant meanings were pondered. Several arguments were observed for euthanasia or assisted suicide from the perspectives of nurses. These arguments were grouped based on the proponent and opponent of euthanasia or assisted suicide practice. In addition, there were a number of factors such as age, gender, specialty, and nurses’ decisions which found their importance. Nurses’ perspectives on euthanasia and assisted suicide are a matter of attention and debate as they occupy a central position and spend most of their time in the care of end-of-life patients. Our findings will enable nurses to engage in the euthanasia practice on its appropriate ground and its debate as well. Additionally, our findings are pragmatically essential for the policy makers and healthcare professionals.